(3GdpbnQi dbGUO Ce GdbQis - (3eMH GdOjf GdWHQj , CMeO Hf YHO Gddg Hf eMeO GdWHQj,J (B694 (3g` s ((3eMeO Hf bGSe GdTQja GdHfRQJi s)
(3ChdgG (B:s
(3bGd GdTjN CMeO Hf YHO Gddg GdWHQi GdTGaYi GdMeO ddg PiGdaVd hGdEfYGe hGdLdGd hGdEcQGe s
(3BNQgG (B:s
(3hjfJgi HHGH eG LGA ai GdfRhd HfeQI hhGdgGLQI (B: (3ETJOGO GdMQ YfO fUa GdfgGQ hGddg CYde s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI Ydi fSNI cJHJ ef fSNI GdeUfas
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs